Evaluating Particle Size - Baker, Scott; Herrman, Tim J. (My University, 2002)
This publication describes the equipment, procedure, costs, and interpretation of particle size analysis.
MF2051_2002_05
Keywords: MF2051; Crops; Equipment and structures; MF